Global microRNA expression profiling in the liver biopsies of hepatitis B virus–infected patients suggests specific microRNA signatures for viral persistence and hepatocellular injury. Issue 5 (1st April 2018) - Singh, Avishek Kumar; Rooge, Sheetalnath Babasaheb; Varshney, Aditi; Vasudevan, Madavan; Bhardwaj, Ankit; Venugopal, Senthil Kumar; Trehanpati, Nirupama; Kumar, Manoj; Geffers, Robert; Kumar, Vijay; Sarin, Shiv Kumar
Abstract : Hepatitis B virus (HBV) can manipulate the microRNA (miRNA) regulatory networks in infected cells to create a permissive environment for viral replication, cellular injury, disease onset, and its progression. The aim of the present study was to understand the miRNA networks and their target genes in the liver of hepatitis B patients involved in HBV replication, liver injury, and liver fibrosis. We investigated differentially expressed miRNAs by microarray in liver biopsy samples from different stages of HBV infection and liver disease (immune‐tolerant [n = 8], acute viral hepatitis [n = 8], no fibrosis [n = 16], early [F1+F2, n = 19] or late [F3+F4, n = 14] fibrosis, and healthy controls [n = 7]). miRNA expression levels were analyzed by unsupervised principal component analysis and hierarchical clustering. Analysis of miRNA–mRNA regulatory networks identified 17 miRNAs and 18 target gene interactions with four distinct nodes, each representing a stage‐specific gene regulation during disease progression. The immune‐tolerant group showed elevated miR‐199a‐5p, miR‐221‐3p, and Let‐7a‐3p levels, which could target genes involved in innate immune response and viral replication. In the acute viral hepatitis group, miR‐125b‐5p and miR‐3613‐3p were up, whereas miR‐940 was down, which might affect cell proliferation through the signal transducer and activator of transcription 3 pathway. In early fibrosis, miR‐34b‐3p, miR‐1224‐3p, and miR‐1227‐3p were up, while miR‐499a‐5p was down, which together possibly mediate chronic inflammation. In advanced fibrosis, miR‐1, miR‐10b‐5p, miR‐96‐5p, miR‐133b, and miR‐671‐5p were up, while miR‐20b‐5p and miR‐455‐3p were down, possibly allowing chronic disease progression. Interestingly, only 8 of 17 liver‐specific miRNAs exhibited a similar expression pattern in patient sera. Conclusion : miRNA signatures identified in this study corroborate previous findings and provide fresh insight into the understanding of HBV‐associated liver diseases which may be helpful in developing early‐stage disease diagnostics and targeted therapeutics. (Hepatology 2018;67:1695‐1709)